Promoted exchange reaction between alkanethiolate self-assembled monolayers and an azide-bearing substituent - Yan, Rui; Le Pleux, Loïc; Mayor, Marcel; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2016)
The possibility of ultraviolet (UV) light promoted exchange reaction (UVPER) between the primary alkanethiolate (AT) self-assembled monolayers (SAMs) and an azide-functionalized substituent (12-azido-1-dodecanethiol, C12N3), capable of click reaction with ethynyl-bearing species, is demonstrated. This reaction resulted in the mixed AT/C12N3 films, with the portion of C12N3 precisely controlled by selection of a suitable UV dose. As the primary matrix, either nonsubstituted or oligo(ethylene glycol) (OEG)-substituted AT SAMs were used, targeting mixed SAMs of chemical and biological significance. To demonstrate the flexibility of the approach, UV light with two different wavelengths (254 and 375 nm) was used, applied to the nonsubstituted and OEG-substituted AT SAMs, respectively. The surface density of the chemically active azide groups embedded in the nonreactive primary matrix could be varied according to the composition of the mixed SAMs, as demonstrated by the subsequent click reaction between these SAMs and several representative functional moieties bearing a suitable group for the click reaction with azide. For the OEG-AT/C12N3 films, this resulted in the preparation of templates for specific protein adsorption, comprising biotin-bearing moieties embedded in the protein-repelling OEG-AT matrix. The density of the biotin receptors was varied according to the density of the C12N3 moieties. The templates exhibited much higher affinity to the specific protein (avidin) as compared to a nonspecific one. The surface density of avidin could be varied in accordance with the density of the biotin receptors, i.e., directly controlled by the UV dose within the UVPER procedure. The entire approach was extended to lithography, relying on a commercial maskless UV lithography setup. Representative gradient patterns of specifically attached avidin in the protein-repelling OEG-AT matrix were fabricated.
Gesehen am 25.02.2021